Heteropterys arcuata (Malpighiaceae): a new species from the dry forests of northeastern Brazil - Pessoa, Cleiton; Amorim, André Márcio (Phytotaxa, 2016)
A new species of Heteropterys series Rhodopetalis from the Northeast Region of Brazil is described and illustrated, and its geographical distribution is presented. The species can be recognized by its tomentose to glabrescent leaves with short petioles, flowers with pedicels 2.5–4.8 mm long, posterior petal with abaxially slightly carinate or smooth limb, stamens with short filaments and uniformly dark (red) connectives, the samara with an oblique and strongly curved dorsal wing and a nut that is deltoid or rounded, rugose, and without winglets. The diagnostic characters of the species of Heteropterys series Rhodopetalis are also discussed.